História e magia no cotidiano da Igreja Evangélica Assembléia de Deus em São Mateus - Barbosa, Francisco José (2008)
This work has as main objective to analyze the history of the Assembly of God Gospel Church in Brazil, mainly in their first fifty years, when it gained an expressive growth. Being the Assembly of God and the Christian Congregation in Brazil the most ancient and the biggest Pentecostal churches of Brazil, from them the Brazilian Pentecostal matrix were formed, being the Assembly of God the main responsible. However, the Assembly of God is not a unique nor an homogeneous church, it is multiple in different aspects like the Assembly movement from 1911 to 1946 and the Assembly institution from 1946 to 1989. The Assembly of God Madureira Ministry, at São Mateus, São Paulo, is a church that arises between 1947 and 1948, tied with the Assembly of God Gospel Church Madureira s Ministry, Brás field, São Paulo, obtaining its emancipation in 1964, becoming a church directly linked to Madureira s National Convention. Regarding to the specific objectives, this work sets out to analyze the relation between the church leader s charisma with the church growth and to set out the survival of popular magic or institutionalized miracles in the everyday life of the church. Through this analysis it was possible to conclude that the present research contributed to demonstrate that the institutionalized religion has its place and prestige but it is a place, among others, necessary to demarcate the celebration and the rite.